Analisis Implementasi Aplikasi Jarkomdat Untuk Pelaporan Berita Acara Klarifikasi (BA) Pada Bagian Dukcapil di PT Telkomsat Bogor - Neneng Susi Riswanti; Mokhamad Hendayun; Chandra Hendriyani (Jurnal Sekretaris dan Administrasi Bisnis, 2022)
The rapid development of technology in the digital era is pushing for changes in the way it works from conventional to computerized in the management of Clarification Minutes (BA) very helpful to companies, one of which is in the storage of BA through the Data Communication Network (Jarkomdat) application. The technology applied can provide benefits consisting of data security and cost savings. The purpose of this study was to determine how the implementation of BA incoming letters, BA letter management, and BA Soft Copy (SC) letter storage using the Jarkomdat application. Besides, to find out how to report BA Hard Copy (HC). The method used in this research is qualitative research and descriptive approach. Data collection techniques used include observation, direct observation at PT Telkomsat Bogor for 310 hours, literature study by taking references from company documents, books, related journals, interviews with employees of PT Telkomsat's Dukcapil section, and documentation by recording audio, taking photos, looking for data in the form of notes. The results showed that the management of BA using the Jarkomdat application and reporting of BA letters conducted by PT Telkomsat Bogor in the digital era currently facilitates the work process so that it becomes more effective and efficient and the company's goals can run well.